(untitled) (Bangladesh Medical Journal, 2009)
Present study was conducted to evaluate the accuracy of Electronic Apex Locator to measure the root canal length in presence of blood, an unavoidable event during extirpation of vital pulp. A number of sixty (60) previously untreated extracted human maxillary and mandibular permanent mature anterior teeth having more or less straight roots with single root canal were included in the study. Root canal lengths were measured using a no. 15 k-file (Mani Inc, Tokyo Japan) in all the teeth until it was just visible through apical foramen that was confirmed by viewing them in Stereomicroscope. The measurements obtained by the Stereomicroscope of all teeth were consider as the ‘Gold standard’ and was also consider as the actual length of those teeth. Using an Electronic Apex locator (Foramatron D 10, Percell, USA) was used to measure the canal length of the same sixty teeth introducing human blood into the canal. Now the measurements taken by Electronic Apex locator (EAL) in presence of blood were compared with the actual length taken by the stereomicroscope and difference in the error length compared with stereomicroscopic length were calculated in a range from -0.5mm to >1 mm. It was observed that working length measurements by EAL in presence of blood within canal mostly remain within clinically acceptable range (± 0.5 mm). DOI: 10.3329/bmj.v37i1.3602 Bangladesh Medical Journal 37(1) 2008 15-18